Using Oral History to Assess Community Impact: A Conversation with Beverly C. Tyler, Historian, Three Village Historical Society (Engaged Scholar Journal: Community-Engaged Research, Teaching, and Learning, 2017)
This article examines the impact of an acquisition by Special Collections at Stony Brook University Libraries on community relations. The department acquired two historically important letters about the Culper Spy Ring, an intelligence gathering effort on Long Island, New York, initiated by George Washington during the American Revolutionary War. Through a guided conversation with local historian Beverly C. Tyler, the authors gained insights on how the letters influenced the community’s re-telling of history and the development of new exhibitions and programming. The conversation also provided context for the relationship between the university and its neighbors. The narrative developed into a significant asset in its own right, in the form of an oral history that provides evidence of a previously undocumented facet of university-community engagement over time.